2024
DOI: 10.1002/pros.24683
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate alleviates experimental autoimmune prostatitis by inhibiting oxidative stress and NLRP3 inflammasome activation via the Nrf2/HO‐1 pathway

Xiaoliang Hua,
Jiong Zhang,
Juan Chen
et al.

Abstract: BackgroundChronic prostatitis and chronic pelvic pain syndrome (CP/CPPS) leads to severe discomfort in males and loss of sperm quality. Current therapeutic options have failed to achieve satisfactory results. Sodium butyrate (NaB) plays a beneficial role in reducing inflammation, increasing antioxidant capacities, and improving organ dysfunction; additionally NaB has good safety prospects and great potential for clinical application. The purpose of the current research was to study the effect of NaB on CP/CPPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…It indicated that SERT could relieve the inflammatory response of LPS-stimulated RWPE-1 cells. Furthermore, EAP mice model, a common in vivo model for CP, 27 , 41 was built to further explore the effect and mechanism of SERT on CP. Our data confirmed that SERT treatment could reduce pain response, improve depression-like symptoms, relieve local prostate inflammation, inhibit the proliferation and promote apoptosis of prostate tissues in EAP mice.…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that SERT could relieve the inflammatory response of LPS-stimulated RWPE-1 cells. Furthermore, EAP mice model, a common in vivo model for CP, 27 , 41 was built to further explore the effect and mechanism of SERT on CP. Our data confirmed that SERT treatment could reduce pain response, improve depression-like symptoms, relieve local prostate inflammation, inhibit the proliferation and promote apoptosis of prostate tissues in EAP mice.…”
Section: Discussionmentioning
confidence: 99%